Dasar Pertimbangan Hukum Hakim Menjatuhkan Putusan Lepas dari Segala Tuntutan Hukum Terdakwa dalam Perkara Pencurian - Fristia Berdian Tamza; M Fadhol Rachman Akbar (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
One of the most important outcomes in the criminal justice system is the acquittal of a defendant in a theft case. This study aims to analyze the basis for the judge's legal considerations in making decisions. The method used is a literature study by reviewing various legal literature, laws and regulations, and relevant court decisions. The results of the analysis show that the judge considered several factors, including: insufficient evidence that points directly to the defendant, reasonable doubts about the defendant's involvement in the crime, and the principle of the presumption of innocence. This decision was taken as a form of protection of human rights and justice. Finally, this study concludes that a decision that passes all legal charges not only reflects the substantive aspects of the law, but also shows the judge's commitment to the principles of justice and protection of human rights.